2006
DOI: 10.1590/s1516-14392006000100013
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization and interactions in Ti- and TiH2-hydroxyapatite vacuum sintered composites

Abstract: Titanium/hydroxyapatite (HAP) composites are candidate materials for biomedical applications as implants and hard tissue substitutes since they combine the good mechanical properties and biocompatibility of Ti with the excellent HAP bioactivity and osteointegration. In powder metallurgy processing of these composites, HAP decomposition promoted by Ti during powder sintering is found. In a previous work Ti-50v%HAP greens of 60% theoretical density (dT) were vacuum sintered at 1150 °C and formation of CaO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
0
27
1
4
Order By: Relevance
“…The formation of Ti x P y phase(s) was also pointed out in composites produced with Ti and HA powders [10][11][12][13][14] . Some researchers report the presence of phases like Ti 4 P 3 or Ti 5 P 3 12 , or Ti 3 P 4 10 without any convincing analyses.…”
Section: In Vitro Testmentioning
confidence: 78%
See 1 more Smart Citation
“…The formation of Ti x P y phase(s) was also pointed out in composites produced with Ti and HA powders [10][11][12][13][14] . Some researchers report the presence of phases like Ti 4 P 3 or Ti 5 P 3 12 , or Ti 3 P 4 10 without any convincing analyses.…”
Section: In Vitro Testmentioning
confidence: 78%
“…This combination can be achieved by a powder metallurgy technique using appropriate mixtures of titanium and calcium phosphate powders. Many titanium composites containing hidroxiapatite, calcium phosphates or a mixture of varying contents of calcium and phosphorous compounds were synthesized through powder metallurgy under different processing conditions [9][10][11][12][13][14][15][16][17][18][19] . Although reporting densification and microstructure of biomaterials fabricated with various parameters, these investigations still cover a limited number of conditions such as raw materials, processing methods, particles size and their chemical and morphologic characteristics, which can lead to different results.…”
Section: Introductionmentioning
confidence: 99%
“…The porous titanium scaffold used in this study had a porosity of 36% and a mean interconnected pore diameter of 480 µm, allowing nutrients to enter the porous structure and form new bone. Earlier results we published about processing of scaffolds and porous coatings indicated that the size and quantity of titanium and spacer powders affect the resulting pore quantity and morphology 30,31,32 . Porous coatings with 11 to 24% porosity and pore sizes of 56 to 120 µm were produced with large titanium particles (500 µm) but without using spacer particles.…”
Section: Discussionmentioning
confidence: 99%
“…O pó de hidreto de titânio foi obtido pela hidrogenação a 500 o C de finos de esponja de titânio, seguida pela moagem por 6 horas. O diâmetro médio das partí-culas de TiH 2 , medido por difração a laser, foi de aproximadamente 15 µm [11].…”
Section: Materiais Utilizados E Misturaunclassified
“…Os trabalhos existentes [8,11] se limitaram basicamente ao estudo das fases formadas em compósitos fabricados com hidroxiapatita micrométrica. Para isso usaram geralmente quantidades iguais ou superiores a 10% em volume de fosfatos de cál-cio.…”
Section: Introductionunclassified